Sustained magnetic fields reveal separate sites for sound level and temporal regularity in human auditory cortex - Gutschalk, Alexander; Patterson, Roy D.; Rupp, André; Uppenkamp, Stefan; Scherg, Michael (NeuroImage, 2002)
Magnetoencephalographywas used to investigate the relationship between the sustained magnetic field in auditory cortex and the perception of periodic sounds. The response to regular and irregular click trains was measured at three sound intensities. Two separate sources were isolated adjacent to primary auditory cortex: One, located in lateral Heschl's gyrus, was particularly sensitive to regularity and largely insensitive to sound level. The second, located just posterior to the first in planum temporale, was particularly sensitive to sound level and largely insensitive to regularity. This double dissociation to the same stimuli indicates that the two sources represent separate mechanisms; the first would appear to be involved with pitch perception and the second with loudness. The delay of the offset of the sustained field was found to increase with interclick interval up to 200 ms at least, which suggests that the sustained field offset represents a sophisticated offset-monitoring mechanism rather than simply the cessation of stimulation.
Gesehen am 10.03.2021